The pharmacokinetics of orally administered ivermectin in African elephants (loxodonta Africana): Implications for parasite elimination - Gandolf, A. Rae (2009)
Loxodonta africana are susceptible to a wide variety of parasites that are often treated with the broad spectrum antiparasitic ivermectin (IVM) based on empirical knowledge. The objectives of this study were to 1) measure plasma IVM levels following administration of 0.1 mg/kg IVM p.o., 2) compare plasma IVM levels following administration with regular versus restricted feed rations, 3) measure IVM excretion in feces, and 4) use these findings to generate dosing recommendations for this species. Using a crossover design, six African elephants were divided into two groups. Ivermectin was administered and typical grain rations were either provided or withheld for 2 hr. Blood and fecal samples were collected for 7 days following drug administration. After a 5-wk washout period, groups were switched and the procedure repeated. Plasma and fecal IVM were analyzed using high-performance liquid chromatography. There was no statistically significant difference detected in the pharmacokinetic data between the fed and fasted groups. Peak plasma concentration, area under the curve, and half-life for plasma ranged between 5.41-8.49 ng/ml, 17.1-20.3 ng × day/ml, and 3.12-4.47 day, respectively. High IVM concentrations were detected in feces. The peak concentration values in feces were between 264-311-fold higher than those obtained in plasma. The comparatively large area under the curve and short time to maximum concentration in feces indicate elimination prior to absorption of much of the drug. Plasma IVM concentrations were low when compared to other species. Based on these findings, administration of 0.2-0.4 mg/kg p.o. should be appropriate for eliminating many types of parasites in elephants, and could minimize development of parasite resistance.